2017
DOI: 10.17265/2332-7839/2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Prevalence and Risk Factors of Depression Symptoms among NCAA Division I Collegiate Athletes

Abstract: This study aimed to determine an overall prevalence rate for depression symptoms among National Collegiate Athletic Association (NCAA) Division I collegiate athletes while also assessing various risk factors that may increase an athlete's vulnerability to depression. Using a sample of 950 NCAA Division I athletes, it was found that 33.2% of athletes experienced symptoms of depression, contradicting findings from previous studies that have suggested a prevalence rate lower than the general college population. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…In light of all the risk factors, student-athletes are at risk for anxiety, depression, drug and alcohol use, and eating disorders (Strohle, 2019). Research has found that more than 30% of student-athletes present with depressive symptoms (Cox et al, 2017), between 30 to 50% of student-athletes have experienced anxiety (Davoren & Hwang, 2014), and almost 60% of female student-athletes are at risk for an eating disorder (National Eating Disorders Association, 2022). Studies have also found that student-athletes participate in high-risk binge-drinking (Druckman et al, 2015;Ford, 2007) and drug use (Gill, 2009;Yusko et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In light of all the risk factors, student-athletes are at risk for anxiety, depression, drug and alcohol use, and eating disorders (Strohle, 2019). Research has found that more than 30% of student-athletes present with depressive symptoms (Cox et al, 2017), between 30 to 50% of student-athletes have experienced anxiety (Davoren & Hwang, 2014), and almost 60% of female student-athletes are at risk for an eating disorder (National Eating Disorders Association, 2022). Studies have also found that student-athletes participate in high-risk binge-drinking (Druckman et al, 2015;Ford, 2007) and drug use (Gill, 2009;Yusko et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The NCAA has declared mental health support one of its top priorities for athletics (Henry, 2020), as the rising number of mental health diagnoses and suicides on college campuses has been labeled as a major public health concern (Liu et al, 2019). For instance, over 30% of 950 NCAA Division I student-athletes experience symptoms of depression (Brown, 2014;Cox et al, 2017), and over 50% have experienced "overwhelming" anxiety in the last year (Brown, 2014). The use of counseling services in colleges across the U.S. has increased significantly, with over half of students who seek help leaving with a severe psychological diagnosis (Rudick and Dannels, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Though the literature suggests there may be differences between male and female athletes in general, the topic remains underexplored in the population of collegiate athletes. This atrisk population faces unique psychological and environmental circumstances and it is crucial to better understand their experiences to provide optimal care after injury [10].…”
Section: Introductionmentioning
confidence: 99%